2018
DOI: 10.1016/j.celrep.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Migratory Dendritic Cells, Group 1 Innate Lymphoid Cells, and Inflammatory Monocytes Collaborate to Recruit NK Cells to the Virus-Infected Lymph Node

Abstract: Summary Circulating natural killer (NK) cells help protect the host from lympho-hematogenous acute viral diseases by rapidly entering the draining lymph node (dLN) to curb virus dissemination. Here we identified a highly choreographed mechanism underlying this process. Using footpad infection with ectromelia virus, a pathogenic DNA virus of mice, we show that TLR9/MyD88 sensing induces NKG2D ligands in virus-infected, skin-derived migratory dendritic cells (mDCs) to induce production of IFN-γ by classical NK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 36 publications
6
45
0
Order By: Relevance
“…We found that cGAS deficiency resulted in significantly decreased, but not absent, transcription of the IFN-I genes Ifna4 (Fig 2A), Ifna-non4 ( Fig 2B) and Ifnb1 (Fig 2C), which at this time point are mostly produced by infected iMOs [16]. However, cGAS deficiency did not affect IFN-γ gene expression ( Fig 2D), which is produced mostly by NK cells [17,19,29]. Different to WT mice, Cgas -/mice did not upregulate expression of the ISGs Ifit3 (Fig 2E), Irf7 ( Fig 2F) Isg15 (Fig 2G), and Mx1 ( Fig 2H) suggesting that the induction of ISGs by IFN-I and IFNγ may be non-overlapping in vivo.…”
Section: Cgas -/Mice Have a Defective Ifn-i And Isg Response In The Dmentioning
confidence: 83%
See 2 more Smart Citations
“…We found that cGAS deficiency resulted in significantly decreased, but not absent, transcription of the IFN-I genes Ifna4 (Fig 2A), Ifna-non4 ( Fig 2B) and Ifnb1 (Fig 2C), which at this time point are mostly produced by infected iMOs [16]. However, cGAS deficiency did not affect IFN-γ gene expression ( Fig 2D), which is produced mostly by NK cells [17,19,29]. Different to WT mice, Cgas -/mice did not upregulate expression of the ISGs Ifit3 (Fig 2E), Irf7 ( Fig 2F) Isg15 (Fig 2G), and Mx1 ( Fig 2H) suggesting that the induction of ISGs by IFN-I and IFNγ may be non-overlapping in vivo.…”
Section: Cgas -/Mice Have a Defective Ifn-i And Isg Response In The Dmentioning
confidence: 83%
“…To ensure that the significant decrease in IFN-I and ISG expression is inherently due to cGAS deficiency and not a challenge-specific phenomenon, we inoculated B6 and Cgas -/ mice with either ECTV or TLR9 agonist CpG and found that CpG inoculation in the footpad does not induce IFN-I or ISG expression at 2 d post challenge (Il12 expression was used as a positive control and was found to be upregulated in both B6 and Cgas -/mice) (S1 Fig). cGAS deficiency did not affect the transcription of the chemokine genes Ccl2 (Fig 2I) and Ccl7 ( Fig 2J) that are important for iMO recruitment [16], or Cxcl9 (Fig 2K), which is important for NK cell recruitment and dependent on IFN-γ during ECTV infection [17]. Also, cGAS deficiency did not affect the transcription of the pro-inflammatory cytokine genes Il12 (Fig 2L), Il6 ( Fig 2M) and Tnf (Fig 2N).…”
Section: Cgas -/Mice Have a Defective Ifn-i And Isg Response In The Dmentioning
confidence: 92%
See 1 more Smart Citation
“…Another novel finding of our work is the requirement for both type I and II IFNs to sustain mannan-induced lymphocyte accrual and LN expansion. This signature strikingly resembles antiviral responses and is not the type of response typically associated with anti-fungal immunity (11,13).…”
Section: Discussionmentioning
confidence: 93%
“…The dLN has been thoroughly scrutinized for its capacity to host adaptive immune responses, but recent reports highlight that activation of immune cells in the peripheral tissue and migration of these cells to the dLN also elicit an antigen-independent lymph node innate response (LIR) (5)(6)(7)(8)(9)(10)(11)(12)(13). Albeit poorly characterized, LIR consists of at least two components: antigen-independent LN expansion and establishment of a pro-inflammatory milieu, which are both critical for the establishment of an effective adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%